Teaching and learning strategies of organic reaction mechanism in pre-university chemistry: a scoping review - Hassan, N.M.H. Nik; Talib, O.; Muhamad, M.M.; Kamarudin, N. (Akademi Sains Malaysia, 2024)
Teaching Organic Chemistry has always been viewed as difficult to teach, where learners are frequently repelled by the topic’s high level of complexity, which appears to discriminate against the subject. Over the years, changes have been made from textbook-driven curriculum to activity-based learning for continuing meaningful learning provided in the Organic Chemistry classroom. This study aims to map the literature on teaching and learning strategies of Organic Reaction Mechanism (ORM) to be incorporated into a proposed module (ORM Module) between the year 2012 up to 2021. A computer-assisted literature search using Scopus, Google Scholar, EBSCOhost, and ProQuest was performed. Additionally, Arksey and O’Malley’s (2005) five-stage framework guided the scoping review approach. The data extracted were respected to study characteristics, inclusion, and exclusion criteria of “organic reaction mechanisms” OR “mechanisms of reactions” keywords. Out of 784 records found in four databases, only 55 were suitable for full-text review, and 17 studies were finally included. Five key strategies for teaching ORM were identified: electron-pushing formalism (EPF), patterns of reactivity, technology integration, problem-solving, and self-regulated learning (SRL), along with six related teaching and learning activities. The findings of this study can be utilised for future development of the ORM Module. Further studies are recommended to investigate the interconnectedness of Organic Chemistry and other research areas.